STRONG SOCIAL POLICY AND SPIRITUAL EDUCATION STRATEGY (Scientific journal of the Fergana State University, 2025)
This article explores the fact that the emphasis on education and upbringing in the world is a strategic requirement for a strong social policy, due to the conditions of today's turbulent times. At a new stage of development of Uzbekistan, attention to the issue of education is taking a new level. This shows the effectiveness of achieving the consequentiality of the spiritual education strategy.